THE EFFORTS OF THE KINGDOM OF SAUDI ARABIA THROUGH VISION 2030 TO REDUCE THE KINGDOM’S OIL DEPENDENCY AND ITS IMPACT ON THE MIDDLE EAST’S STABILITY - Rahmadani Putri, Anastasia (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2020)
Oil has become the most valuable natural resource for human and state survival. In response to the Kingdom’s heavy reliance on oil, the de facto leader of Saudi Arabia, Crown Prince Mohammed bin Salman announced an ambitious vision to end their dependence on oil and hold an essential role in transforming Saudi Arabia’s oil-based economy into a modern economy. This article is intended to examine Saudi Arabia’s effort and progress to accomplish the ambitious goals that require society reform within itself. In addition, this study will also attempt to draw the linkage on how economic reformation by one specific country will affect its relations with the other states, which leads to favorable conditions in promoting peace. Thus, in consideration of this article’s purposes, a theory introduced by neoliberalist Robert Keohane and Joseph S Nye called Complex Interdependence, and Endogenous Growth theory will be used in analyzing the willingness of Saudi Arabia to change its stance from being addicted to oil and having more cooperation with other states along with non-state actors as well. By developing its economy and citizens’ livelihood, Saudi will attract more partners to achieve Vision 2030 goals and promote peace in the international system.